Literature study of Islamic Economics and Finance Research - Ahmad Muhajir; Andri Soemitra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study tries to look at research related to Islamic economics and finance in scientific journals. The study used descriptive statistical analysis based on 100 published articles related to Islamic economics and finance in national and international journals. The entire sample journal publication has been published over the past 5 years from 2017 to 2021. The results showed that Islamic Economic and financial research is still dominated by the theme of Hajj (20%). Waqf (18%) followed by Islamic banks (15%), zakat ( 15%), Islamic capital market (12%) Islamic accounting (10%) and Islamic insurance (10%). In addition, the comparison between qualitative research and combined methods is still much less than with quantitative approaches.